Financialisation and the financial and economic crises: The case of Germany - Daniel Detzer; Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
This study on Germany examines the long-run changes between the financial and the non-financial sectors of the economy, and in particular the effects of these changes on the macroeconomic developments that have led or contributed to the financial crisis starting in 2007 and the Great Recession in 2008/09. The first part provides some descriptive statistics on real GDP growth, on the growth contributions of the main demand aggregates, and the financial balances of the macroeconomic sectors since the early 1980s, and it classifies the German type of development as 'export-led mercantilist'. The second part examines the effects of an increasing dominance of finance since the early/mid 1990s on income distribution, investment in capital stock, consumption and the current account in more detail. The third part links the longrun developments with the financial and economic crisis and examines the causes of the quick recovery in Germany.
Keywords: D31; D33; D43; E25; E61; E63; E64; E65; F40; F43; 330; current account imbalances; distribution of income; finance-dominated capitalism; financialisation; financial and economic crisis; Germany; Kaleckian distribution theory; trade balance